2013
DOI: 10.2147/opth.s43106
|View full text |Cite
|
Sign up to set email alerts
|

Application of 2-octyl-cyanoacrylate for corneal perforation and glaucoma filtering bleb leak

Abstract: BackgroundThis paper reports on the efficacy of a tissue adhesive, 2-octyl-cyanoacrylate, in the treatment of corneal perforation and glaucoma filtering bleb leak.MethodsTwo eyes from two patients with corneal perforation or laceration and two eyes from two patients with bleb leak were included. The patients underwent application of 2-octyl-cyanoacrylate onto the perforated or leaking site, and a hydrogel contact lens was applied as a bandage. We also evaluated the in vitro cell toxicity of 2-octyl-cyanoacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The hyperdry device and sterilization by γ‐irradiation at 25 kGy, which has been recommended for terminal sterilization of medical products, can completely prevent known transmissible infections, and no adverse effects have been reported in patients who received HD‐AM grafts . Bacteriologic test also indicated that 25 kGy γ‐irradiation achieved to complete sterilization(data not shown).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The hyperdry device and sterilization by γ‐irradiation at 25 kGy, which has been recommended for terminal sterilization of medical products, can completely prevent known transmissible infections, and no adverse effects have been reported in patients who received HD‐AM grafts . Bacteriologic test also indicated that 25 kGy γ‐irradiation achieved to complete sterilization(data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…No recurrence of pterygium was noted, and no signs of infection and rejection were observed during the follow-up period. HD-AM has been found to be a safe and useful biological material for human ocular surface disease, [29][30][31]37 for human dura mater undergoing neurosurgery, 32 for human bony surface the mastoid cavity in canal wall down tympanoplasty, 33,34 and for surgical defects of the human oral mucosa. 35,36 Many surgeons said that HD-AM is easy to care for treatment and it is able to short the operating time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations